Communication Peculiarities of Adolescents with Mental Retardation in Student Group - Olga Babiak (Newinera Publisher, 2020)
The paper deals with the communication peculiarities of mentally retarded adolescents, the maturity of motivational, operational and cognitive components of their communication. A carried out empirical study made it possible to assess the extent and quality of communication components in the adolescents with mental retardation. Using theoretical and empirical research methods, features of the functioning of the motivational, operational and cognitive communication components were defined. The motivational component helps to identify personal and social needs that determine the communication of a personality, the operational one – communicative behavior that meets the society behavior pattern standards and is carried out by means of self-regulation; the cognitive one – communicative competence and culture, which are determined by communicative qualities, knowledge, skills, and abilities. The research results give grounds for arguing that the mentally retarded adolescents’ communication is insufficiently mature, in other words, it is characterized by dominant behavior forms with negative attitude towards peers, low need for interaction, affective behavior manifestations, proneness to conflicts, limited communication skills; increased level of aggressiveness, which is expressed in affective, frustrated forms of deviations in emotional-volitional sphere; immaturity of communicative means of making contacts. The low level of communication components maturity results in significant difficulties in interaction, which in turn affects person’s further socialization and integration into the society.